Application of the Willis Covered Stent in the Treatment of Blood Blister-Like Aneurysms: A Single-Center Experience - Fang, Wei; Yu, Jia; Liu, Yufeng; Sun, Peng; Yang, Zijian; Zhao, Zhenwei; He, Yue; Deng, Jianping; Zhang, Tao (Frontiers in Neurology, 2022)
Objective：To evaluate the effectiveness of the Willis covered stent in the treatment of ruptured blood blister-like aneurysms (BBAs) of the internal carotid artery (ICA). Method：The clinical data of 16 patients consecutively treated with Willis covered stents （WCSs）from December 2015 to January 2019 were retrospectively analyzed. Clinical data and angiographic findings were analyzed by two experienced neuroradiologists and neurosurgeons, including age, sex, Hunt and Hess (H&H) grade at admission, modified Rankin scale (mRS) score, aneurysm size and location, the diameter of the patent artery in proximal and distal ends, stent size, rate of aneurysm occlusion, procedure related complications, and follow-up. Results: All the 16 patients (5 males, 11 females) with ICA BBAs underwent Willis covered stent deployment successfully. The median age was 49 years (range, 29–72). All patients had complete aneurysm occlusion on immediate postoperative angiography. Anterior choroidal artery（AChA）was occluded in one patient accidentally while no obvious neurological dysfunction was observed. However, this patient underwent subarachnoid hemorrhage 1 day after treatment; endoleak and aneurysm recurred, and the patient died 10 days later. Therefore, the effective rate of Willis covered stent treatment was 93.8% (15/16), and treatmentprocedure-related complications were found in rate was 6.3% (1/16). Moreover，one patient was urgently treated because of accidental aneurysm rupture after anesthesia, and external ventricular drainage was then performed postoperatively. OneAnother patient developed coma and hemiplegia 3 days after treatment, with emergency angiography showing in-stent thrombosis and internal carotid artery occlusion which was recanalized with arterial rt-PA thrombolysis; the patient recovered completely. The clinical follow-up period was 3-30 months in 14 patients. The mRS scores were 0 in 12 patients (85.7%) and 4 in 1 case (7.1%), while 1 patient (7.1%) died 6 months postoperatively for unknown reason. Angiographic follow-up was performed in 13 patients, and no recurrence was observed. However, internal carotid artery occlusion without neurological deficit was observed in one patient. Conclusion: Based on careful preoperative evaluation, appropriate WCS size selection and precise surgical operation，Willis covered stents may provide an alternative and effective solution for blood blister-like aneurysms via aneurysm isolation and ICA reconstruction immediately; howeverHowever, further follow-up studies with larger samples are required.